Scholarly Communication: The Use and Non-Use of E-Print Archives for the Dissemination of Scientific Information - Ibironke Lawal (Issues in Science and Technology Librarianship)
This study surveyed a randomly chosen sample from a population of 240,000 scholars in nine scientific disciplines from private and public colleges and universities across the United States and Canada. The disciplines included physics/astronomy, chemistry, mathematics/computer science, engineering, cognitive science/psychology, and biological sciences. The survey sought to determine use and non-use of e-print archives in the different disciplines. Results show that 18 percent of the researchers use at least one archive while 82 percent do not use any. Scholars in physics use e-print archives the most and chemistry the least. ArXiv receives the most use and authors' web sites the least use. Reasons for use include dissemination of research results, visibility, and exposure of authors. Reasons for non-use include publishers' policies and technology constraints.